The industry of testing and mutual recognition in southern Europe - Cruz, Joaquin Manuel (The Grove - Working Papers on English Studies, 2016)
Following the publication of the Common European Framework of Reference, Spain’s central government has been unable to unify common policies for foreign language requirements in Spanish Higher Education. Language requirements are in Spain both partially unregulated and deemed compulsory to finish Higher education degrees. In the absence of national policies, different areas of the country have implemented different policies in this respect and, inevitably, Spanish universities have developed their own internal legislation, high-quality suites of language tests and mutual recognition systems. These vary greatly from university to university, and are now competing in the industry of testing at both a national and a global level. The universities in Andalusia, one of the 17 autonomous communities of Spain, have been able to agree on a set of unified criteria which favors mutual recognition of language certifications for +13K candidates on a yearly basis and have driven policy makers’ attention to their network, which is being regulated a posteriori.